Functional analysis of the emerging roles for the KISS1/KISS1R signaling pathway in cancer metastasis. (March 2022) - Li, Zhenxi; Liu, Jing; Inuzuka, Hiroyuki; Wei, Wenyi
Abstract: Cancer metastasis, a process that primary tumor cells disseminate to secondary organs, is the most lethal and least effectively treated characteristic of human cancers. Kisspeptins are proteins encoded by the KISS1 gene that was originally described as a melanoma metastasis suppressor gene. Then, Kisspeptins were discovered as the natural ligands of the G-protein-coupled receptor 54 (GPR54) that is also called KISS1R. The KISS1/KISS1R signaling is essential to control GnRH secretion during puberty and to establish mammalian reproductive function through the hypothalamic-pituitary-gonadal (HPG) axis. Although KISS1 primarily plays a suppressive role in the metastasis progression in several cancer types, emerging evidence indicates that the physiological effect of KISS1/KISS1R in cancer metastasis is tissue context-dependent and still controversial. Here, we will discuss the epigenetic mechanism involved in the regulation of KISS1 gene expression, the context-dependent role of KISS1/KISS1R, prometastasis/anti-metastasis signaling pathways of KISS1/KISS1R, and the perspective anticancer therapeutics via targeting KISS1/KISS1R.